A future European FDI screening system: solution or problem? - Carlos Esplugues (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2019)
The establishment of a mechanism at the European level for screening FDI, on the grounds of national security and public order, constitutes a major step in implementing the EU investment policy. To create an effective system, it must be based on clear common rules, provide certainty and ensure judicial redress.
Keywords: 330